2004
DOI: 10.1063/1.1669255
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial diodes of a half-metallic ferromagnet on an oxide semiconductor

Abstract: We report on the fabrication and electrical characterization of epitaxial Schottky diodes of a half-metallic ferromagnet on an oxide semiconductor. La0.67Sr0.33MnO3 thin films are grown by pulsed laser deposition on niobium-doped SrTiO3 semiconductor substrates with two doping concentrations and a TiO2 surface termination. The current across the diodes is dominated by thermionic emission and shows high rectification and low reverse bias leakage. At room temperature, the Schottky barrier height is 0.95 eV (0.65… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
33
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 14 publications
6
33
0
Order By: Relevance
“…13 In all cases, the rectification direction is consistent with that of a Schottky junction with regarding Sr(Ti,Nb)O 3 and metallic perovskites as n-type semiconductor and deep work-function metals, respectively. The present SrRuO 3 /Sr(Ti,Nb)O 3 junction is considered to be one of them.…”
supporting
confidence: 53%
“…13 In all cases, the rectification direction is consistent with that of a Schottky junction with regarding Sr(Ti,Nb)O 3 and metallic perovskites as n-type semiconductor and deep work-function metals, respectively. The present SrRuO 3 /Sr(Ti,Nb)O 3 junction is considered to be one of them.…”
supporting
confidence: 53%
“…Similar deviations of the current-voltage characteristics from an ideal thermionic emission have been previously reported in heterojunctions of NSTO with other transitionmetal oxides, [7][8][9][10]26 and thermionic-field emission (thermally assisted tunneling) has been proposed as a possible mechanism that may explain the observed results. 8 In particular, as described below in more detail, a thermionic-field emission process would explain the almost temperature-independent slope observed in log 10 J − V curves at low temperatures [see Fig.…”
Section: Resultssupporting
confidence: 64%
“…8,30 The small values could result from the high electric field existing in the space-charge region, 31 or from the presence of a low-permittivity layer at the NSTO surface. 7,32 Interestingly, although ε r was considered to be temperature independent in previous analyses of similar J − V characteristics, capacitance measurements indicated that ε r has a temperature dependence similar to the one we obtain here. 8 Note also that in order to obtain the dielectric permittivity values, we used Eq.…”
Section: Resultssupporting
confidence: 50%
See 1 more Smart Citation
“…Similar observations of a decrease in SBH and an increase in the ideality factor at low temperatures have also been reported for different combinations of manganite/Nb:STO interfaces. [19][20][21] Hot electron transmission, recorded using BEEM, across a LSMO (13 u.c. )/Nb:STO Schottky interface is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%